From talent to creative cities: toward a conceptual framework - Sebastien Chantelot; Peres Stephanie; Virol Stephane (European Regional Science Association (ERSA), 2011)
The creative class approach (Florida, 2002b) has led to many developments. Therefore, measurement of creativity (Chantelot, 2010), economic influence of creative people in urban (Marlet & Van Woerkens, 2007) and rural (McGranahan & Wojan, 2007) environments, or creative people geography (Chantelot & al., 2010) and factors that shape it (Boshma & Fritsch, 2009) have been investigated. Increasingly, these works tend to substitute static considerations (who and where are creative people?) to dynamic approaches (what do the creative people?). Creativity mainly comes from talent (Florida, 2002a) but creative production is generated through collective process where social interactions, learning and diffusion of ideas predominate (Cohendet & Simon, 2008). The transition from individual to collective process particularly appears to be driven by cities, defined as privileged theaters of creativity (Hall, 1998). Hence, cities managing to convert micro or individuals ideas to macro or collective outputs can be defined as "creative cities". It sheds light on the determinant role of cities in attracting, organizing and producing creative people in order to experience virtuous path of economic competitiveness (Lucas, 1988). This communication aims to give a conceptual framework to characterize creative cities. At the urban level, it formalizes the micro / macro transition: micro level consists in talent, which includes both individuals with a creative profession directly involved in the production of innovations, new knowledge and ideas - both related to the industrial or scientific sphere (the 'creative core') and arts (the Bohemians) - or in its implementation and management on the market (the 'creative professionals' - ibid.). Therefore, the aim is to connect creative or innovative clusters of firms (where creative pro and core mainly work) with creative urban districts characterized by intense cultural and artistic, driven by Bohemians, and places of socialization and urban regeneration. This connection can be ensured by a meso level characterized by the presence of communities that facilitate the micro/macro-ideas transition to the market. The definition of these three different levels, the construction of their measure, and the way to identify their respective roles and interactions that shape the creative city structure the dynamic conceptual model we propose here.
Keywords: 330